PEMANFAATAN SAMPAH SISA PERSEMBAHYANGAN MENJADI ECO-ENZYME SEBAGAI PUPUK CAIR RAMAH LINGKUNGAN DI DESA ADAT BULELENG - Putu Dewi Merlyna Yuda Pramesti; Jean Nihana Mulyo Putri Manalu; Made Ary Meitriana (Universitas Mataram, 2026)
Bali is one of the largest contributors to waste in Indonesia. One of the major factors driving this issue is the high frequency of religious activities among the Balinese community. TPS 3R NEKAD KEDAS is a waste management facility located in the Buleleng Traditional Village. The greatest amount of waste processed at TPS 3R NEKAD KEDAS consists of organic waste, totaling 416.29 kg per day. Organic waste can be managed by converting it into eco-enzymes, which can be used as liquid fertilizer. The methods used in this community service program included socialization, training, and mentoring. The participants of this activity consisted of 10 KMP members and representatives from 14 banjars in the Buleleng Traditional Village. The purpose of this program was to provide knowledge about organic waste management, the utilization of organic waste generated from religious offerings, and the packaging of fermented eco-enzymes that can be used as liquid fertilizer. The program resulted in successful eco-enzyme production, indicated by a characteristic fermentation odor and the absence of microbial contamination. Participants were also able to harvest and package the eco-enzymes. Based on the evaluation results, there was an increase of 44% in participants' knowledge and attitudes toward the use of eco-enzymes as liquid fertilizer, while participants' skills in producing eco-enzymes increased by 94%.